1989
DOI: 10.1007/bf02535763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fats on fatty acid composition and Δ5 desaturase in normal and diabetic rats

Abstract: We have studied the effect of various diets on the phospholipid fatty acid composition and in vitro delta 5 desaturase activity of hepatic microsomes derived either from the normal or streptozotocin-induced diabetic rat. The diets studied were the standard rat chow diet and a basal fat-free diet supplemented either with 20 percent saturated fat, 20 percent unsaturated fat, or 20 percent menhaden oil. Phospholipid fatty acid composition analysis revealed that the normal rat fed the saturated fat or menhaden oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…This decrease in PUFAs involved all of the functionally important fatty acids, including arachidonic acid, EPA and DHA. These observations are in agreement with data reported in diabetic patients [23], and are due probably to reduced 6 -desaturase and 5 -desaturase activities related to diabetes and to increased peroxidation of PUFA by free radicals [24][25][26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This decrease in PUFAs involved all of the functionally important fatty acids, including arachidonic acid, EPA and DHA. These observations are in agreement with data reported in diabetic patients [23], and are due probably to reduced 6 -desaturase and 5 -desaturase activities related to diabetes and to increased peroxidation of PUFA by free radicals [24][25][26].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, it has been reported that fish oil induces changes in cholesterol metabolism in rat liver leading to increases in biliary excretion of cholesterol [37]. Indeed, the dietary EPAX intake by mothers and their macrosomic pups induced a large increase in n − 3 PUFA levels, followed by a large decrease in arachidonic acid, in agreement with previous results [11,24]. DHA has been shown to inhibit the conversion of C 18:2n−6 into C 20:4n−6 by decreasing 6 -desaturase activity [38], which may explain the increased C 18:2n−6 and decreased C 20:4n−6 in serum and liver of the diabetic rats fed the EPAX diet.…”
Section: Discussionsupporting
confidence: 82%
“…This shows that the A 6 desaturase activity is relatively unaffected by PUFA deficiency, while that of `5 5 desaturase is reduced. Reduction in ,5 5 desaturase activity has also been proposed in rats fed PUFA deficient diets (Dang et al 1989). Feeding the commercial diet to fish virtually diminished elongation and desaturation in both polar and neutral lipid classes, showing the impof tance of diet on lipogenic processes.…”
Section: Resultsmentioning
confidence: 97%
“…Some of these changes, the decreases in palmitoleate and arachidonate and the increases in linoleate and eicosatrienoate are probably due to diminished A 9 , A 6 , and A 5 desaturase activities in the diabetic liver (4,5). For nomenclature of fatty acids referred to in this article, please see Table 1.…”
mentioning
confidence: 98%